Release of antral and duodenal gastrin in response to an intestinal meal. - Llanos, O L (1977)
In dogs prepared with isolated, innervated antral pouches, intraduodenal perfusion with liver extract at pH 7, with the atrum buffered at pH 7, resulted in a significant release of gastrin selectively from the antrum and from the duodenum. Acidification of the meal to pH 1 abolished both antral and duodenal gastrin release, whereas acidification of the antrum abolished only the antral gastrin response. After antrectomy, liver extract at pH 7 caused a diminished but significant release of duodenal gastrin. These studies provide evidence that an intestinal meal may release (in addition to a specific intestinal phase hormone) gastrin from the intestine, and from antrum, by means of a pH-sensitive mechanism which may involve a humoral agent (enterobombesin?) from the small bowel.